2020
DOI: 10.1186/s12931-020-01457-2
|View full text |Cite
|
Sign up to set email alerts
|

Cold-inducible RNA-binding protein might determine the severity and the presences of major/minor criteria for severe community-acquired pneumonia and best predicted mortality

Abstract: Background: Severity of community-acquired pneumonia (CAP) depends on microbial pathogenicity, load and virulence, and immune responses. The Infectious Disease Society of America and the American Thoracic Society (IDSA/ATS) minor criteria responsible for clinical triage of patients with CAP are of unequal weight in predicting mortality. It is unclear whether the IDSA/ATS major/minor criteria might be strongly and positively associated with the immune responses. It is warranted to explore this intriguing hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…Several previous preclinical and clinical studies have also demonstrated that hypoxia, both acute and chronic, induce upregulation of intracellular CIRP expression and that acute hypoxia result in release of eCIRP to the extracellular space and circulation (12,13,24). Also, in line with our results, pre-pandemic studies in sepsis and community acquired pneumonia, found that elevated eCIRP levels were prognostic for developing a severe disease or lethal outcome (16,17).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several previous preclinical and clinical studies have also demonstrated that hypoxia, both acute and chronic, induce upregulation of intracellular CIRP expression and that acute hypoxia result in release of eCIRP to the extracellular space and circulation (12,13,24). Also, in line with our results, pre-pandemic studies in sepsis and community acquired pneumonia, found that elevated eCIRP levels were prognostic for developing a severe disease or lethal outcome (16,17).…”
Section: Discussionsupporting
confidence: 90%
“…When first described serum levels of eCIRP were undetectable in healthy volunteers, while increased in patients with hemorrhagic shock admitted to the intensive care unit (ICU) (12). Later, serum eCIRP levels have been associated with severe disease and poor prognosis in patients with sepsis, community-acquired pneumonia, and acute pancreatitis (16)(17)(18)(19). Extracellular cold-inducible RNA-binding protein knock out mice (eCIRP-/-) are protected against inflammatory disease (15,20), and neutralizing antibodies against eCIRP are shown to attenuate inflammation and improve survival in animal models of hemorrhagic shock, sepsis, and hepatic ischemia (12,21).…”
Section: Introductionmentioning
confidence: 99%
“…e most obvious increase is in children [20]. Studies have also shown [21] that SAA has a certain e indicators such as MLD and double lung V20 in the radiotherapy plan have been widely used in clinical treatment plan evaluation. Since most studies mainly analyze the dose and volume parameters of the irradiated lung tissue from the perspective of radiation physics, it has certain guiding significance.…”
Section: Discussionmentioning
confidence: 99%
“…There might be another, yet undefined connection between exRNA and the systemic cytokine storm, hemorrhage, and sepsis that are the major causes of death in COVID-19 patients. This potential connection is based on the role of "coldinducible-RNA binding protein" (CIRP) and its relevance for community-acquired pneumonia, whose severity is related to microbial pathogenicity and virus load (Guo et al, 2020). As a typical DAMP, nuclear CIRP is liberated by macrophages and other cells upon stress and promotes inflammatory responses (cytokine release) via the TLR4-myeloid differentiation factor 2 complex, also causing endothelial dysfunction (Qiang et al, 2013; Figure 1).…”
Section: Perspectives and Hypotheses: Possible Contributions Of Exrnamentioning
confidence: 99%